Celebrating Adam Watkins' 2nd Birthday in Backyard - Watkins, Howard::::::::: (1980)
Christine Watkins washing large Miracle Maid pot in old kitchen Shows breakfast nook, stainless steel sink and small counter space; orange flower wall paper